Phenomenological Study: The Role of Informal Economic Education in the Sustainability of Donggala Silk Weaving Business - Andi Annisa Sulolipu; Andi Tenri Ampa; Agussalim Agussalim (JURNAL PENDIDIKAN IPS, 2025)
This study seeks to elucidate the significance of informal economic education in preserving the sustainability of the Donggala Silk Weaving enterprise as a cultural heritage and a livelihood source for the community. The employed methodology is a qualitative technique utilizing a phenomenological study, conducted through in-depth interviews with silk weaving entrepreneurs who inherited their weaving talents from their family. The findings indicate that the process of skill inheritance occurs naturally, in an unstructured and voluntary manner, yet successfully conveys information between generations. Children engage in weaving activities from a young age through direct observation and practice, allowing the talent to evolve into a primary source of income. From a phenomenological standpoint, weaving is regarded not merely as an economic endeavor, but also as an integral aspect of cultural identity, a vehicle for familial socialization, and a symbol of pride for the Kaili community. This study reveals that the sustainability of traditional enterprises is significantly affected by the subjective significance attributed to abilities, rather than solely by market forces. These findings theoretically enhance the literature on informal economic education within the framework of local culture. The study underscores the necessity of amalgamating informal education with contemporary support mechanisms, including training, digitization, and empowerment programs. Additional research is advised to investigate intergenerational dynamics and technical interventions in facilitating the transformation of weaving enterprises in the context of globalization.